Measurement of coarse aggregates movement characteristics within asphalt mixture using digital image processing methods. (15th October 2020) - Shi, Liwan; Wang, Duanyi; Jin, Changning; Li, Ben; Liang, Hehao
Highlights: The meso-parameters of coarse aggregates movement characteristics within asphalt mixture were proposed. The movement characteristics of coarse aggregates within three different asphalt mixtures were compared. A meso-structural model of coarse aggregate movement was proposed. The correlations between meso-parameters of coarse aggregates movement and rut depth were analyzed. Abstract: The movement of aggregates plays an important role in the permanent deformation of asphalt mixture. To provide a reference for the design of asphalt mixture, this study conducted in-depth analyses of the mechanisms involved in coarse aggregate movement and rutting subjected to load by using digital image processing (DIP) technique. The movement characteristics of coarse aggregates within different asphalt mixtures were investigated from a mesoscopic perspective, and correlations between meso-parameters of coarse aggregates movement and rut depth (RD) were analyzed. Finally, a meso-structural model of coarse aggregate movement was proposed. The results indicated that the anti-rutting performance of asphalt mixture is closely related to the meso-movement parameters of coarse aggregates. The movement regions of coarse aggregates subjected to load can be divided into a compacted flow zone, uplifted zone, and a disturbed zone, depending on the movement characteristics of coarse aggregates. There is an obvious linear correlation between the RD and the movement parameters of coarse aggregates in the compacted flow and uplifted zones. Material design measures of asphalt mixture can effectively improve the rutting resistance include using materials that have a coarse gradation and asphalt with high cohesion.